2021
DOI: 10.1101/2021.07.31.454564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A pore-forming protein drives macropinocytosis to facilitate toad water maintaining

Abstract: Maintaining water balance is a real challenge for amphibians in terrestrial environments. Our previous studies with toad Bombina maxima discovered a secretory aerolysin family pore-forming protein and trefoil factor complex βγ-CAT, which is assembled under tight regulation depending on environmental cues. Here we report an unexpected role for βγ-CAT in toad water maintaining. Deletion of toad skin secretions, in which βγ-CAT is a major component, increased animal mortality under hypertonic stress. βγ-CAT was c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(29 citation statements)
references
References 49 publications
3
25
1
Order By: Relevance
“…These results indicated that βγ-CAT not only was able to stimulate the cellular import of albumin-bound FAs but also mediated the export of albumin and FAs in the form of exosomes. These results were different from our previous findings that when toad B. maxima urinary bladder epithelial cells were treated with 50 nM purified βγ-CAT, augmented exosome release was determined but no enrichment of cargo molecules (dextran) was observed (Zhao et al, 2021). This discrepancy clearly reflected that when cells are treated with βγ-CAT, the specific biological outcomes are dependent on the type of cells and the cell surroundings.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…These results indicated that βγ-CAT not only was able to stimulate the cellular import of albumin-bound FAs but also mediated the export of albumin and FAs in the form of exosomes. These results were different from our previous findings that when toad B. maxima urinary bladder epithelial cells were treated with 50 nM purified βγ-CAT, augmented exosome release was determined but no enrichment of cargo molecules (dextran) was observed (Zhao et al, 2021). This discrepancy clearly reflected that when cells are treated with βγ-CAT, the specific biological outcomes are dependent on the type of cells and the cell surroundings.…”
Section: Resultscontrasting
confidence: 99%
“…We then assayed the ability of βγ-CAT to stimulate macropinocytosis in hCMEC/D3 and Caco-2 cells. Consistent with our previous findings (Zhao et al, 2021), βγ-CAT greatly increased the internalization of the micropinocytosis marker 70-kDa dextran, which was inhibited by addition of the macropinocytosis inhibitor wortmannin (WORT; a PI3K inhibitor) (Supplementary Fig. S2D).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations